Development of real time audio signal measuring instrument and signal conditioning circuit: article / Muhamad Fairuz Ahmad Bakri - Ahmad Bakri, Muhamad Fairuz (2005)
This paper presents the development of real time audio signal measuring instrument and signal conditioning circuit. The design undergoes several processes and displayed using computer via interfacing system. The process also involve with the used of Artificial Intelligent (AI) technique, i.e. Fuzzy Logic. MATLAB Fuzzy Toolbox and Simulink are use to realized real-time simulation and displayed the results in the form of fuzzy classification. The raw signal which is in term of frequency is detected by sensor and then was amplified, filtered and purified through signal conditioning circuitry. The output signal from signal conditioning circuitry is then injected to the interfacing system circuit. Interfacing system circuit is use as a medium to allow communication between signal conditioning circuitry and personal computer. All the conversion necessary to produce compatible signal for computer communication are solve in the interfacing circuit. Those signal then classified using fuzzy logic membership function.